Run with the hunted : a Charles Bukowski reader - Bukowski, Charles (Ecco, 2003)
"The best of Bukowski's novels, stories, and poems, this collection reads like an autobiography, relating the extraordinary story of his life and offering a sometimes harrowing, invariably exhilarating reading experience. A must for this counterculture idol's legion of fans." -- Amazon.com viewed August 26, 2020.